2010
DOI: 10.1038/labinvest.2009.137
|View full text |Cite
|
Sign up to set email alerts
|

CC-PLA2-1 and CC-PLA2-2, two Cerastes cerastes venom-derived phospholipases A2, inhibit angiogenesis both in vitro and in vivo

Abstract: Integrins are essential in the complex multistep process of angiogenesis and are thus attractive targets for the development of antiangiogenic therapies. Integrins are antagonized by disintegrins and C-type lectin-like proteins, two protein families from snake venom. Here, we report that CC-PLA2-1 and CC-PLA2-2, two novel secreted phospholipases A 2 (PLA 2 ) isolated from Cerastes cerastes venom, also showed anti-integrin activity. Indeed, both PLA 2 s efficiently inhibited human brain microvascular endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 40 publications
(56 reference statements)
0
31
0
2
Order By: Relevance
“…Mammalian PLA 2 was identified as a ligand for αvβ3 and α4β1 integrins and receptor-binding sites have already been localized (Saegusa et al, 2008). Recent studies revealed that PLA 2 from Cerastes cerastes and Macrovipera lebetina transmediterranea snake venoms also inhibit αvβ3 and α5β1 integrins, although binding sites for these molecules remain unknown (Bazaa et al, 2009; Kessentini-Zouari et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Mammalian PLA 2 was identified as a ligand for αvβ3 and α4β1 integrins and receptor-binding sites have already been localized (Saegusa et al, 2008). Recent studies revealed that PLA 2 from Cerastes cerastes and Macrovipera lebetina transmediterranea snake venoms also inhibit αvβ3 and α5β1 integrins, although binding sites for these molecules remain unknown (Bazaa et al, 2009; Kessentini-Zouari et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, phospholipases A 2 (PLA 2 s, EC 3.1.1.4) have been demonstrated to modulate integrins which are essential protagonists of the complex multistep process of angiogenesis, the major target for the development of anticancer therapies [21, 27, 28] (Figure 1). …”
Section: Tunisian Viperidae Snake Venom Proteinsmentioning
confidence: 99%
“…The most interesting are the antitumor and antiangiogenic activities which involve integrins [27, 28]. …”
Section: Pharmacological Activities Of Spla2 From Tunisian Vipersmentioning
confidence: 99%
See 1 more Smart Citation
“…PLA 2 belongs to a superfamily of enzymes responsible for hydrolyzing the sn -2 fatty acids of membrane phospholipids [70] . These enzymes are known to play multiple roles that include angiogenesis [71] , cell death [72] and inflammation [70] . An experimental model of envenomation in rats has been used to show that a PLA 2 responsible for intravascular hemolysis is present in the venom of L. obliqua [73] .…”
Section: Platelet Aggregation Dysfunctionmentioning
confidence: 99%